2012
DOI: 10.1074/jbc.m111.308064
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Induces Interleukin-27 through Cyclooxygenase-2 and Protein Kinase A Signaling

Abstract: We previously reported that IL-27, which belongs to the IL-12 family of cytokines, is elevated in the serum of patients infected with influenza A virus (IAV). Here, we show that the expression of IL-27 was significantly up-regulated in A549 human lung epithelial cells and human peripheral blood mononuclear cells infected with IAV. Additionally, IAV triggered IL-27 expression through protein kinase A and cAMP-response element-binding protein signaling, which was mediated by cyclooxygenase-2-derived prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 51 publications
4
79
0
Order By: Relevance
“…The blot is a representative of three experiments with similar results. *p , 0.05. inhibits IAV replication by activating STAT1/2 phosphorylation and PKR phosphorylation (20). We also showed that IL-27 protein levels were elevated in patients with HBV infection and that HBV enhances the expression of IL-27 in several cell types, including THP-1, HepG2, Huh7, and HEK293T cells (36).…”
Section: Il-27 Enhances the Expression Of Ifn-l1 Receptors Il-28r1 Anmentioning
confidence: 68%
See 1 more Smart Citation
“…The blot is a representative of three experiments with similar results. *p , 0.05. inhibits IAV replication by activating STAT1/2 phosphorylation and PKR phosphorylation (20). We also showed that IL-27 protein levels were elevated in patients with HBV infection and that HBV enhances the expression of IL-27 in several cell types, including THP-1, HepG2, Huh7, and HEK293T cells (36).…”
Section: Il-27 Enhances the Expression Of Ifn-l1 Receptors Il-28r1 Anmentioning
confidence: 68%
“…IL-27 has therapeutic potential through various mechanisms: inhibiting replication of HIV (12) and hepatitis C virus (HCV) (13), enhancing antitumor immune responses (14), directing antiproliferative effects on tumors (15)(16)(17), and reducing the inflammation associated with experimental autoimmune arthritis (18,19). We recently demonstrated that during influenza A virus (IAV) infection, IL-27 is strongly induced through cyclooxygenase-2 (COX-2)-and protein kinase A (PKA)-signaling pathways (20).…”
mentioning
confidence: 99%
“…Similarly, a previous study demonstrated that IL-27 has INF-like response as it induces antiviral genes including PKR, 2'-5' Oligoadenylate synthase and myxovirus protein 1 (Frank et al, 2010).Indeed, IL-27 was shown to be a potent inducer of IFN-gamma, which inhibits the viral replication (Tang et al, 2003). IL-27 was shown recently to inhibit human influenza virus, HIV, and HCV replication by inducing an IFN-like response (Fakruddin et al, 2007;Imamichi et al, 2008;Frank et al, 2010;Liu et al, 2012).The effect of SNP of IL27p28 (especially c.-964A/G (rs153109) on progression of various diseases such asassociation between HBV and HCC (Peng et al, 2013), HBV susceptibility and response to HCV genotype 1 therapy (Zicca et al, 2014) has been evaluated. Here we examined the effect of IL-27-p28.rs153109 SNP on the ability of patients infected with HCV genotype 4a to spontaneously resolve their infection.…”
Section: Introductionmentioning
confidence: 84%
“…41 Another research claimed that IL-27 is a novel anti-HIV cytokine that inhibits HIV replication by activating multiple interferon-inducible genes in macrophages. 42 Furthermore, Le Texier and associates showed that IL-27 along with TGFβ1 play a role in model of rodent cardiac allograft tolerance that their expression correlates with inhibition of Th17 differentiation and with expansion of regulatory CD4+ CD25+ T cells. 18 It also has been proposed that IL-27 can show as effective therapeutic agent suppresses differentiation of Th17 cells in autoimmune diseases like Sjögren syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…41 The role of IL-27 in the pathogenesis of other viral infections show its prominent role in removing viruses, for example; study of the role of IL-27 in influenza virus type A replication and gene expression showed inhibition and antiviral function of IL-27 which enforced by activation of STAT1/2/3. 42 Wang and associates carried out a gene expression profiling study and found that IL-27 serum levels were significantly higher in HBV-infected patients in comparing with healthy controls. 7 Zhu and associates determined the correlation between HBV infection and IL-27 gene expression, using semiquantitative RT-PCR and ELISA method which results showed that IL-27 was significantly elevated in patients as compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%